2019
DOI: 10.1111/tbed.13139
|View full text |Cite
|
Sign up to set email alerts
|

Bioaerosol and surface sampling for the surveillance of influenza A virus in swine

Abstract: SUMMARY Influenza A virus in swine is of significant importance to human and veterinary public health. Environmental sampling techniques that prove practical would enhance surveillance for influenza viruses in swine. The primary objective of this study was to demonstrate the feasibility of bioaerosol and surface sampling for the detection of influenza virus in swine barns with a secondary objective of piloting a mobile application for data collection. Sampling was conducted at a large swine operation between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Pig oral fluid sampling is an effective and efficient approach to identify pathogens among pigs (Ramirez et al, 2012). While we did not include pig oral secretion sampling in this study, other studies assessing the ecology of influenza A virus in swine farms have shown agreement in molecular detections between pig oral fluid samples and bioaerosol samples (Anderson et al, 2018;Prost et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Pig oral fluid sampling is an effective and efficient approach to identify pathogens among pigs (Ramirez et al, 2012). While we did not include pig oral secretion sampling in this study, other studies assessing the ecology of influenza A virus in swine farms have shown agreement in molecular detections between pig oral fluid samples and bioaerosol samples (Anderson et al, 2018;Prost et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A or Porcine Circovirus Type 2 (PCV2) in swine (López-Lorenzo et al, 2019;Neira et al, 2016;Prost et al, 2019). Likewise, the airborne detection of pathogens has been performed on viruses such as PCV2 (Verreault et al, 2010) or Avian Influenza A (Blachere et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the environmental detection of pathogens have been carried out on viruses which affect other animal species, like Aleutian mink disease virus (AMDV) (Prieto et al., 2014, 2017), Influenza A or Porcine Circovirus Type 2 (PCV2) in swine (López‐Lorenzo et al., 2019; Neira et al., 2016; Prost et al., 2019). Likewise, the airborne detection of pathogens has been performed on viruses such as PCV2 (Verreault et al., 2010) or Avian Influenza A (Blachere et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…That is, as a result of pigs' normal exploratory behavior, i.e., smelling, tasting, biting, and rooting, environmental diagnostic targets are collected in the buccal cavity [28] -some of which are subsequently passed onto the rope and into the oral fluid specimen. This is not a negative attribute of the specimen; to the contrary, the presence of such material broadens the diagnostic utility of the oral fluid sample [29,30].…”
Section: Oral Fluidsmentioning
confidence: 99%